Kearifan Lokal Masyarakat Dayak Ngaju Dari Sistem Pertanian Tradisional Untuk Pendapatan Keluarga di Buntut Bali Kabupaten Katingan Kalimantan Tengah: Local Wisdom of the Dayak Ngaju Community from Traditional Agricultural Systems for Family Income in Buntut Bali, Katingan Regency, Central Kalimantan - Yanarita, Yanarita; Tanduh, Yusintha; Silvianingsih, Yosefin Ari; Pidjath, Chartina; Madiyawati, Milad; Sudomo, Muhammad Fadhil Amiruddin; Afentina, Afentina (HUTAN TROPIKA, 2024)
Local wisdom is knowledge and practices passed down by a group that serves as an identity and strategy carried out in meeting the needs of daily life. This research highlights the local wisdom of the Dayak Ngaju people of Buntut Bali village, Katingan, who use traditional farming systems for their livelihoods. This traditional farming system can not only be adapted to local conditions, but more importantly is able to contribute to food security and local ecological sustainability. The research methodology used was descriptive qualitative method with a field approach through observation and in-depth interviews with farmers who are members of the “Pamaran” farmer group. Data collected included crop types, cropping patterns and constraints faced by farmers. The results revealed that the Ngaju-Dayak community's cropping pattern is a polyculture farming system consisting of annual and seasonal crops. There are 15 types of annual plants dominated by durian and banana. While 14 types of annual crops are managed in rotation and intermittently, according to soil conditions and seasons. Simple economic formulas about the income obtained from the application of traditional agriculture show that crop yields cannot be guaranteed to be profitable, because the results are influenced by how many trees bear fruit that are seasonal, such as durian, langsat and rambutan. In traditional farming systems, there are also often wild plants that are used by the community that cannot be planted but are very popular as vegetables, such as: teken parei. Local wisdom in traditional farming systems needs to be maintained for the preservation of local species and increased innovation in the maintenance and improvement of crop products, especially fruits